ICT-Based Learning Support Applications By Utilizing Sevima Edlink At SMPIT INSAN RABBANI - NASUTION, WINDA SUCI LESTARI (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The Covid-19 pandemic that has hit the world has had a tremendous effect on lives. PSBB (Large-Scale Social Restrictions) followed by WFH (Work From Home) and also online learning are the consequences of the Covid- 19 pandemic. The very rapid progress in the world of information technology which is triggered by the internet and smart phones has changed all aspects of human life that lead to digital life. The knowledge and abilities of SMPIT Insan Rabbani teachers in the use and utilization of information and communication technology (ICT), especially SEVIMA EdLink, are still lacking. SEVIMA EdLink as a support for online learning that adapts to the needs of the digitalization era to produce the skills of teachers and students as a skilled and skilled workforce that is able to adapt to the demands and needs of IT-based learning by considering values including economic value, functional value , psychological value and creative value and innovative value. The results obtained are that theteacher can deliver teaching materials, make assignments and exams anytime and anywhere.